Systemic thrombolytic therapy in treatment of acute limb ischemia: a single-center retrospective observational study - Khaled Attia; Mahmoud Moawad; Walied Khereba (Wolters Kluwer Medknow Publications, 2022)
Background and aim Owing to the increased risk of morbidity and mortality, the treatment of acute limb ischemia (ALI) is challenging. The authors aimed to investigate the outcomes of thrombolysis in the treatment of ALI and limb salvage. Patients and methods A retrospective observational study was conducted to revise the data of 49 patients who underwent catheter-direct thrombolysis for ALI. A total of 33 cases were at lower limb and 16 cases were at upper limb. The assessed outcomes were primary and secondary patency, survival, amputation-free survival, and conversion to surgery. Results The patients were classified according to the Rutherford classification into class I (52%), class IIa (38%), class IIb (8%), and class III (2%). The primary patency was present in 34% of the patients after the first year and 22% after the second year. On the contrary, 28% of the patients were subjected to conversion to open surgery, 8% were subjected to reintervention, and 6% were subjected to amputation within the first month. The mortality rate within 1 month was 6%. The worst primary and secondary patency rates were seen in the prosthetic grafts in addition to vein bypasses, whereas the native artery was the most successful one regarding the primary patency, secondary patency, and amputation-free survival (P<0.05 for each). Conclusion The thrombolysis of vein bypass and prosthetic grafts did not show technical success as that seen with native artery. Additional treatment at the time of thrombolysis was shown to be associated with better outcomes.